Sustainability of post-mining land use and ecotourism - Herdis Herdiansyah; Marikha Ulfah Utami; Joko Tri Haryanto (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2018)
The mining sector can contribute to the state in the form of foreign exchange and state in the form of foreign exchange and funding sources such as royalties, taxes, the expansion of employment and physical development, on the other hand, led to some social and environmental conflicts. One effort to improve environmental conditions in the mining area through revegetation, reclamation and post-mining. Reclamation and post-mining activities must be under the EIA plan, FS, Plans Closure Reclamation and Mine Closure Plan to be used for sustainability and ecotourism. This study was conducted using a collaboration between study literature method and the AHP method. The purpose of this study was to determine the post-mining land use, preferred alternatives for utilization of post-mining land is done through the Analytical Hierarchy Process (AHP) method by analyzing the relationship between three criteria and alternatives. The criteria are selected based on the ecological, socioeconomic and cultural aspects. This is based on the consideration of sustainability and spatial planning. In addition, the alternatives that will be considered as utilization strategies include the efforts to increase the land use.. Secondary data analysis resulted that known to the utilization of post-mining land from various companies such as: the use of pits (void) into water treatment, aquaculture and ecotourism, the usage of land reclamation and mine closure in the form of plateau used as cultivation flora and fauna depends on the utilization zone, which has approved the EIA Document, FS, Plans Closure Reclamation and Mine Closure Plan.